1993
DOI: 10.1111/j.1570-7458.1993.tb00704.x
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of 9 stored product beetles at pitfall trap arenas and their capture in millet

Abstract: Pitfall trap capture for Sitophilus oryzae (L.), S. zeamais (Motschulsky), S. granarius (L.), Tribolium confusum (Duval), T. castaneum (Herbst); Oryzaephilus surinamensis (L.), Cryptolestes pusillus (Schonherr), Rhyzopertha dominica (Fabr.), and Prostephanus truncatus (Horn) in millet was assessed by visual and time‐lapse video recordings. The behaviour of different beetle species in arenas containing millet was monitored over 24 h and the frequency of encounters with the trap rim resulting in capture recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Species-specific responses to trap material are common (Luff 1975, ObengOfori 1993. Glass is normally found to be the most effective material in terms of numbers of individuals captured, and is almost always superior to metals (Luff 1975, Obeng-Ofori 1993. The superiority of glass over other materials is particularly important if live catches are required.…”
Section: Trap Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Species-specific responses to trap material are common (Luff 1975, ObengOfori 1993. Glass is normally found to be the most effective material in terms of numbers of individuals captured, and is almost always superior to metals (Luff 1975, Obeng-Ofori 1993. The superiority of glass over other materials is particularly important if live catches are required.…”
Section: Trap Materialsmentioning
confidence: 99%
“…It has been suggested that the trap rim should be placed 1-7 mm below the level of the substrate surface (Good & Giller 1991, Obeng-Ofori 1993. However, this is normally awkward, and for large numbers of traps may be impractical.…”
Section: The Trap Rimmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an estimate of the probable feed materials available on the range and is carried out by the use of pitfall traps, transect mapping and quadrants. Pitfall traps are used to estimate the quantity of crawling insects and other metazoans which are available in a reference area (Obeng-Ofori, 1994). An area 1 m 2 is used for each estimation.…”
Section: Parameters and Procedures For Direct Assessment Of Scavengeamentioning
confidence: 99%